PENGEMBANGAN MEDIA PEMBELAJARAN P3 (PAPAN PUTAR PINTAR) PADA MATERI PROKLAMASI KEMERDEKAAN DI INDONESIA UNTUK PEMBELAJARAN IPS KELAS IV SDN UNGGULAN KARANGGENENG - Rieke Septi Anggraeni Wilujeng; Arya Setya Nugroho; Nanang Khoirul Umam (Yayasan Nusantara Hasana Berdikari, 2023)
Development of P3 Media (Smart Playboard) on the Material of the Proclamation of Independence in Indonesia for Class 4 Social Studies Learning at SDN Unggulan Karanggeneng. Thesis, Elementary School Teacher Education Program. Faculty of Teacher Training and Education. Muhammadiyah Gresik University (supervised by Mr. Arya Setya Nugroho and Mr. Nanang Khoirul Umam, M.Pd). This study aims to describe the process of development and quality of P3 media on the material for the Proclamation of Independence for fourth grade elementary school students. In 2021/2022. The research model used in this development research is the ADDIE model. The subjects in this study were fourth grade students at SDN Unggulan Karanggeneng, totaling 18 students. The learning model used during implementation uses the first 3 models TGT, IBL, Discussion. The data collection technique for this research is to use validation sheets and student questionnaires. Analysis of the data obtained from the validation sheet of media experts, the graphic aspect obtained a percentage of 90% and the linguistic aspect obtained a percentage of 83.3%. while the presentation aspect material expert validation obtained a percentage of 91.6% and the content feasibility aspect obtained a percentage of 91.6% and the criteria were very good.